SIGNIFICANCE OF SOMA: THE NECTAR OF THE GODS - Supriya Pal (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Soma in ancient India a Plant, of which juice was fundamental offering of the Vedic sacrifices. There was great mysticism and spiritual power surrounding the plant. Soma plant is of great significance; it is defined as a composite of lunar energy. The plant is prominently called the nectar of gods. In scientific terminology, the Soma plant is known as Ephedra Gerardiana. This plant provides numerous boons to people. Soma is a mysterious plant and a hub of numerous medicinal benefits also. Soma plant acquires an elaborative link with the Indian mythological history and culture. Soma drink was prepared by pressing the stalks of the some plant between stones and the juice was filtered through sheep’s woof and then mixed with water milk, curds, ghi, barley and honey. The great scriptures state that great gods including mighty Indra and Agni Deva, used to drink it and they were courageous and immortal because of it. Our great Purāṇas, including Ṛgveda and Gῑtā mention Soma plant’s pious usage for medical and spiritual practices. This plant is considered the elixir of immortality. ‘Soma’ a ritual drink, was considered as the most precious and indispensible entity in the 120 hymns of the Ṛgveda. For example, the 9th maṇḍala of the Ṛgveda is also known as the soma maṇḍala consists of hymns addressed to ‘soma pavamāna’ (purified soma). ‘Soma’ was composed from a plant, most likely hallucinogenic and magical, which caused an overwhelming and empowering feeling of intoxication. This drink was also known as ‘amṛta’ or the wine of immortality. Being considered as the most precious liquid in the universe, soma, was used in all Vedic sacrifices to all gods, specially to Indra, the warrior god, and Agni, the divine representation of fire. Gods consumed the soma in copious quantities to sustain their immortality. ‘Soma’ played an important role in Vedic rituals. Some of the most famous were the consecration of the king (rājasūya) ‘the drink of power’ ritual (vājapeya) and various fire rituals (agniṣṭoma). Due to the supernatural powers bestowed upon those who drank this drink, soma gradually Sturned to be portrayed as a god. In the Ṛgveda, the Vedic god Soma was considered to be the king of plants and the bestower of immortality. Soma’s divine dominion was held over plant life. In the later Vedas, God soma was identified with the moon god, chandra, a god of the flowing waters, a god of inspiration and ecstasy. Soma, as a god, is believed to be the personification of soma juice. Thus few myths have been found in various Vedic texts regarding the origin of Soma as god. Besides, being recognized as an essential entity of Vedic sacrifices and deity soma was also regarded as the king of medicinal herbs and was titled as ‘supervisor of herbs’ by several texts like the Atharvaveda. Thus, we notice that the ‘soma’ was a celebrated plant. It played a vital and an influential role in Vedic tradition and was perceived as a giver of not only immortality but also healthy and long life, happiness, courage, strength and above all considered as the bestower of wisdom, understanding and creativity.